Deprem Yönetmeliklerindeki Zemin Sınıflandırma Kriterlerinin Zemin Büyütmesi Açısından İncelenmesi - Halaç, Başak (Fen Bilimleri Enstitüsü, 2016)
Depremlerin oluşmasını önlemek imkansızdır. Fakat depremin ortaya çıkardığı etkilerini hafifletmek, can kaybı, yaralanma ve zararı azaltmak alınabilecek önlemler sayesinde mümkündür. Bu önlemlerden en önemlisi de depreme dayanıklı yapı tasarımına hakim olmak ve yapılan yapıları bu esaslara göre inşa etmektedir. Türkiye'de son yıllarda yaşanan depremler de göstermiştir ki yapısal hasar, deprem ve yapılaşma özelliklerinin yanında zemin koşullarından da etkilenmektedir. Bir depremin zemin tabakaları içerisinde ilerlerken yapılarda oluşan yıkıcı etkilerinden biri de deprem dalgaları üzerindeki zemin büyütme etkisidir. Zemin büyütme etkisi, deprem dalgalarının genlik, frekans içeriği ve süresinin dalgaların içinden geçtiği zemin tabakalarının fiziksel ve dinamik özelliklerine bağlı olarak değişmesine denmektedir. Zemin büyütmesine neden olan en önemli etkenler, deprem dalgalarının içinden geçtiği zemin tabakalarının yoğunluğu ve rijitlik durumlarıdır. Bir deprem dalgası anakayadan daha az rijit bir zemin tabakasına geçerken deprem dalgası genliği artmakta, frekans içeriği ve süresini değiştirmektedir. Enerjinin korunumu ilkesinden dolayı diğer bir etken ise empedans oranıdır. Anakayanın kayma dalga hızı ve yoğunluğunun çarpımına, yüzeydeki zemin tabakasının kayma dalga hızı ve yoğunluğunun çarpımına olan orana empedans oranı denilmektedir. Empedans oranın birden büyük olması anakayadan daha yumuşak zeminlere geçildiğini ve dalga genliklerinin artacağını göstermektedir. Depremin insan hayatına etkisini azaltmak için depreme dayanıklı yapı tasarımı yaygınlaştırılmalı ve kolaylaştırılmalıdır. Bu sebepten dolayı pek çok ülkede konusunda uzman bilim adamlarından oluşan komitelerin çalışmalarıyla çeşitli yönetmelikler oluşturulmuştur. Günümüzde insanoğlunun hayatını korumak, yaşam kalitesini artırmak ve mal kaybını önlemek adına bu yönetmelikler kullanılmaktadır. Bu çalışmada da üç farklı depreme dayanıklı yapı tasarımı yönetmeliği ele alınarak çalışılmıştır. Bu yönetmelikler sırasıyla; Ulusal Deprem Tehlikesini Azaltma Programı(NEHRP), Eurocode 8 ve Deprem Bölgelerinde Yapılan Binalar Hakkında Yönetmelik (DBYBHY)'dir. Bu çalışmada amaçlanan bu yönetmeliklerdeki zemin sınıflarına ait sınırların zemin büyütme açısından incelenmesidir. Bu amaçla NEHRP ve Eurocode8 için bu yönetmeliklerde belirtilen zemin sınıflarına ait maksimumVs30 (30 m'deki ortalama kayma dalga hızı), DBYBHY için yine bu yönetmelikte verilen maksimum Vs değerleri kullanılarak sınır profilleri, ara değerler kullanılarakta ara profilleri oluşturulmuştur. Bu şekilde toplam 167 tane birbirinden farklı zemin profilleri oluşturulmuş ve bu profillere ait analizler yapılmıştır. Oluşturulan bu profillerin transfer fonksiyonları Shake Analiz programında bir deprem kaydı kullanılarak yapılmış ve transfer fonksiyonları elde edilmiştir. Ara zemin profillerinden elde edilen transfer fonksiyonlar değer ve şekilleri açısından incelenerek bu yönetmeliklerdeki sınıflandırma sınır değerlerine ait transfer fonksiyonları arasında kalıp kalmadığı incelenmiştir. NEHRP zemin sınıflarının tanımlamaları incelendiğinde çok genel tanımlamalar olduğu görülmektedir. Kullanılan zemin profilleri ve bu profiller için üretilen amplifikasyon (transfer) fonksiyonları birlikte incelendiğinde bazı profillerin bir alt sınıfın üst sınır profiliyle aynı frekanslarda aynı zemin büyütme değerlerini verdiği görülmüştür. Buna neden olan profiller ait oldukları sınıfların en alt sınırları olduğu ve alt sınıfın üst sınırını geçmediği için çok büyük önem taşımadığı düşünülmüştür. Eurocode8 zemin sınıflarının tanımlamaları incelendiğinde NEHRP'e oranla daha detaylı tanımlamaların olduğu görülmektedir. Kullanılan zemin profilleri ve bu profillere ait amplifikasyon fonksiyonları ile birlikte incelenmiştir. Bu incelemenin sonucu olarak herhangi bir sınıfa ait olan bazı profillerin, bir alt sınıfın üst sınır profiline ait aynı frekanslardaki (en büyük zemin büyütme değerlerini verdiği frekans) zemin büyütme değerlerinin NEHRP kadar birebir aynı olmasa da yaklaşık olarak aynı zemin büyütme değerini verdiği görülmektedir. DBYBHY ait zemin sınıflarının tanımlamalarına göz gezdirildiğinde diğer iki yönetmeliğe göre daha detaylı tanımlamaların olduğu görülmektedir. Fakat sonuçlar incelendiğinde sınırların diğer iki yönetmelik kadar keskin olmadığı sınıf sınırları arasında birbirine kaymalar olduğu gözlenmektedir. Ardışık farklı iki sınıfta yaklaşık olarak aynı frekanslarda yaklaşık olarak aynı zemin büyütme değerlerine sahip profiller olduğu görülmektedir.

Earthquakes effect people and their environment. Earthquake engineering deals with methods of reducing those effects. Geology, seismology, geotechnical engineering and structural engineering are involved in earthquake engineering. When an earthquake occurs, seismic waves travel from the source to the earth's crust. When these waves reach the ground surface, they produce shaking. This shaking is known as earthquake. The strength and duration of earthquake depends on characteristics of earthquakes (location and size of earthquakes) and on characteristics of local soil. Earthquakes occurred since prehistoric age and will definitely continue in future. It is impossible to prevent the earthquake. But it is possible to prevent to earthquake to disaster if engineers precaution take the required (loss of life, injuries and economic damages). The most important reason which cause damages during earthquakes is the effect of local site conditions on earthquake. An earthquake can be characterized by defining the amplitude, frequency content and the duration. These variations on the amplitude, frequency content and duration of the earthquake can be seen as amplification caused by the local site effects. Defining and designing by taking consideration of effects of local site conditions on damage of earthquakes has an important role to decrease the damage of further possible earthquakes. Nowadays, billions of people throughout in the world live with a significant risk to their lives and property. Because of earthquake not only people's life is at risk but also the health of many local, regional and national economies are at risk. The main reasons of earthquake damages were amplifications factor on the characterics of earthquake and the design of earthquake resistant constructions. It is very important to predict effect of local site condition on the characteristic of input motion. Because of this many countries were considered to importance of earthquake resistant structural design and were began to studies about that. In many countries developed their own design standards to predict and to prevent seismic hazards. In this study three different earthquake resistant structural design regulations were mentioned. Those regulations are National Earthquake Hazard Reduction Program (NEHRP), Eurocode 8 and Regulation about Buildings in Earthquake Zone (DBYBHY). In these regulations' soil classes average shear wave velocity up to 30 m have been given. Soil profiles were created by using soil classification criteria specified in these regulations. First one is European standard series related to construction, Eurocode8: Design of structures for earthquake resistance describes how to design structures in seismic zone, using the limit state design philosophy. It was approved by the European Committee for Standardization on 23 April 2004. Second one is National Earthquake Hazard Reduction Program (NEHRP). Since its creation in 1979, the National Earthquake Hazard Reduction Program has provided a framework for efforts to reduce the risk from earthquakes. The Building Seismic Safety Council (BSSC) is extremely proud to have been selected by the Federal Emergency Management Agency (FEMA) to play a role under NEHRP in improving the seismic resistance of built environment. Third one is Regulations on Buildings to Be Constructed in Earthquake Zone. (DBYBHY). Purpose of this regulation make earthquake resistant design for all building types which will be reconstructed or will be redesigned in earthquake zone and to determine the necessary rules and minimum requirements for the evaluation and improvement of performance of the existing building before or after earthquake. Provisions of this regulations are carried out by The Ministry of Public Works and Settlement (of Turkey). And validity of provisions of DBYBHY for reinforced concrete, steel and masonry building types. In this study, the effects of local site conditions on the soil amplification properties caused by October 19, 1989 Loma Prieta Earthquake are investigated. October 19, 1989 Loma Prieta earthquake's magnitude was 6.9 and the maximum horizontal peak acceleration was 0.49g. To predict soil amplification properties a widely accepted solution technique, that depends on theory of one dimensional wave propagation in horizontally layered, linear viscoelastic medium, called Shake is used for the analysis. Soil transfer (amplification) functions are calculated by using Shake program. Earthquake and soil profiles which were created by using regulation have been analyzed in Shake Analysis program. As a result of these analyses transfer (amplification) function have been obtained. In this thesis main objective was evaluation of the amplification properties of soil classification criteria of the earthquake regulations. Soil profiles have been selected according to soil profile description in soil classes of this regulations. Transfer (amplification) functions have been obtained by applying one Earthquake to this constituted soil profiles. The classification of regulations' limits are consistent whether or not were evaluated by using this transfer (amplification) spectrum. For this occasions to considering that the frequency where is the amplification factors are maximum in the amplification spectrums. When the classification' descriptions of NEHRP were analyzed, obtained that description of regulation are not to be detailed. In the view of such information, thought that this regulations was not useful. However when the results of amplification curves (Transfer Spectrum) of profiles were examined, it appears not to be like that. Soil profiles which are used, together with the amplification curves of the profiles were examined. The result of this, can be seen that some of profiles and the profile of next sub class' upper limit have the same amplification values at same frequency. The reason of this results was soil profiles are the lower limit of the class to which they belong and does not exceed the upper limit of the lower class carried a very big importance for it was thought that. When the classification' descriptions of Eurocode8 were analyzed, observed that description of regulation are more detailed than NEHRP. Soil profiles which are used, together with the amplification curves of the profiles were examined. The result of this, can be seen that some of profiles and the profile of next sub class' upper limit have the approximately same amplification values at the approximately same frequency. It's not like as same as NEHRP classification' soil profiles. Due to this reasons it is considered that regulation is consistent. Also these two regulations shows that layers of soil profiles' depths were very effective for the Transfer Spectrum. When the classification' descriptions of DBYBHY were revised, observed that this regulation' description more detailed than other two regulations'. But the results of the analysis are examined, it is seen that this is not so. This regulation hasn't sharply circumscribed boundaries like other ones. It is seen that this Regulation the class boundaries shifts between each other. it is seen that in two consecutive different classes have approximately the same amplification values at the approximately the same frequencies. The reason is that specifications of shear wave velocity values were thought to be insufficient even though there are specification related to the depth of the soil layers.
Review Of The Soil Classification Criteria In Earthquake Regulations With Respect To Amplification
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2016
Thesis (M.Sc.) -- İstanbul Technical University, Instıtute of Science and Technology, 2016
Keywords: Deprem; Kuvvetli Yer Hareketi; Zemin Büyütmesi; Deprem Yönetmelikleri; NEHRP; Eurocode 8; DBYBHY; Zemin Sınıflandırma Kriterleri; Shake Analiz Programı; Transfer Fonksiyonu.; Earthquake; Ground Motion; Soil Amplificition; Earthquake Regulations; NEHRP; Eurocode 8; DBYBHY; Soil Classification Criteria; Shake Analysis Programme; Transfer Functions.